Pengaruh Paparan Radiasi Gamma dan Pemberian Ekstrak Temulawak (Curcuma xanthorrhiza) terhadap Jenis dan Luas Kurva Radikal Bebas pada Paru-paru Mencit (Mus musculus) - Septiana Kurniasari; Rara Ayu Shabrina (Universitas Sultan Ageng Tirtayasa, 2020)
The interaction of radiation with cells will form free radicals. Free radicals can cause cell damage. The presence of free radicals contained in cells could be detected using Electron Spin Resonance. Antioxidant compounds could minimize free radicals. This study analyzed curcumin extract and gamma radiation exposure on the area of free radical curves in the lungs of mice. Eighty male mice were used in this study and were divisible into three groups, namely the negative control group, the non-extract radiation group, and the extract plus radiation group. Curcumin extract was given at a dose of 1,4 gr/kgBB; 2,0 gr/kgBB; 2,6 gr/kgBB; 3,2 gr/kgBB and 3,8 gr/kgBB. The mice were exposed to gamma radiation for 10, 20, 30, 40, and 50 minutes. The results showed that curcumin extract, which was given as prevention from gamma radiation, reduced the area of the free radical curve from 0,630 cm2 to 0,004 cm2.